Gold Surprises Us - de Theije, Marjo; Morim, Júlia (Journal of Anthropological Films, 2025)
Gold is the cornerstone of Suriname's economy, attracting many Brazilian migrants who seek to improve their lives. Building on a friendship spanning over fifteen years, miner Pretinha and anthropologist Marjo embarked on a collaborative film project focusing on gold lifeways. The film delves into the miners' experiences, highlighting the quest for stability, legal insecurity and complex gender dynamics. Under the direction of Júlia Morim and Marjo de Theije, the filming took place in July 2022, at a gold mine in the Brokopondo region and in Suriname's capital, Paramaribo. Gold Surprises Us explores the miners' relationships with the environment and the future of their communities. By portraying the perspective of the gold miners, challenging common stereotypes of them as Amazonian bandits, this collaboration aims to humanise them and to make discussions about environmental sustainability more inclusive. The film was made as part of the international GOLDMATTERS project (<a href="https://eur04.safelinks.protection.outlook.com/?url=http%3A%2F%2Fgold-matters.org%2F&data=05%7C02%7Cm.c.dietrich%40uva.nl%7C2dd3d88c9e04413a1e4108dd7661a2ac%7Ca0f1cacd618c4403b94576fb3d6874e5%7C0%7C0%7C638796883898999919%7CUnknown%7CTWFpbGZsb3d8eyJFbXB0eU1hcGkiOnRydWUsIlYiOiIwLjAuMDAwMCIsIlAiOiJXaW4zMiIsIkFOIjoiTWFpbCIsIldUIjoyfQ%3D%3D%7C0%7C%7C%7C&sdata=3rkwIc7pFQnsU%2BgbRYNC6MMXacqylhst535m63MrTNw%3D&reserved=0">http://gold-matters.org/), which investigated transformative approaches to sustainability in artisanal and small-scale gold mining across African and Amazonian countries.